2019
DOI: 10.1007/s10450-019-00104-7
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations of n-butane and n-octane adsorbed onto graphite and a molecular model of activated carbon

Abstract: In this work we report results of Monte Carlo simulations of n-butane and n-octane adsorbed onto graphite and a molecular model of activated carbon, with the aim to provide simplified models that will allow the study of these kind of systems with lower computational and time costs. A combination of Coarse Grain models (CG) and Monte Carlo simulations (MC) were used. Adsorbates were reduced from four atoms to one pseudoatom and the adsorbent carbons from two atoms to one pseudoatom. We compare the results betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Among the most studied materials are: MOF [10] [11] [12] [13], zeolites [14] [15], mesoporous silica [16] [17] and activated carbons [18] [19] The focus is put mainly on activated carbons, since they are materials that have a high specific surface area, a wide variety of surface chemistry, and, above all, a relatively low cost [20] [21] [22]. However, activated carbons are amorphous materials and their structures could not be accurately characterized to this day [23]. This lack of characterization leads to the synthesis of activated carbons for specific purposes becomes a complicated task since it is difficult to manage parameters such as the distribution of pore sizes, the aforementioned surface chemistry and even to achieve uniformity in the surfaces specific.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most studied materials are: MOF [10] [11] [12] [13], zeolites [14] [15], mesoporous silica [16] [17] and activated carbons [18] [19] The focus is put mainly on activated carbons, since they are materials that have a high specific surface area, a wide variety of surface chemistry, and, above all, a relatively low cost [20] [21] [22]. However, activated carbons are amorphous materials and their structures could not be accurately characterized to this day [23]. This lack of characterization leads to the synthesis of activated carbons for specific purposes becomes a complicated task since it is difficult to manage parameters such as the distribution of pore sizes, the aforementioned surface chemistry and even to achieve uniformity in the surfaces specific.…”
Section: Introductionmentioning
confidence: 99%
“…-H. Song et al (2002) suggested that adsorbent concentration, temperature, and adsorption time are the main factors affecting the adsorption capacity. Hermosilla et al (2019) studied the isothermal adsorption process of activated carbon on n-butane. The results showed that an increase in n-butane concentration led to a rapid increase in the adsorption of activated carbon.…”
Section: Introductionmentioning
confidence: 99%